West End Walkers 65+: A randomised controlled trial of a primary care-based walking intervention for older adults: Study rationale and design - Rowe David A; McConnachie Alex; Macdonald Hazel; Grealy Madeleine; Grant Margaret P; Granat Malcolm H; Black Karen; Fitzsimons Claire; MacMillan Freya; Shaw Rebecca; Skelton Dawn A; Mutrie Nanette (BMC, 2011)
Abstract Background In Scotland, older adults are a key target group for physical activity intervention due to the large proportion who are inactive. The health benefits of an active lifestyle are well established but more research is required on the most effective interventions to increase activity in older adults. The 'West End Walkers 65+' randomised controlled trial aims to examine the feasibility of delivering a pedometer-based walking intervention to adults aged ≥65 years through a primary care setting and to determine the efficacy of this pilot. The study rationale, protocol and recruitment process are discussed in this paper. Methods/Design The intervention consisted of a 12-week pedometer-based graduated walking programme and physical activity consultations. Participants were randomised into an immediate intervention group (immediate group) or a 12-week waiting list control group (delayed group) who then received the intervention. For the pilot element of this study, the primary outcome measure was pedometer step counts. Secondary outcome measures of sedentary time and physical activity (time spent lying/sitting, standing or walking; activPAL™ monitor), mood (Positive and Negative Affect Schedule), functional ability (Perceived Motor-Efficacy Scale for Older Adults), quality of life (Short-Form (36) Health Survey version 2) and loneliness (UCLA Loneliness Scale) were assessed. Focus groups with participants and semi-structured interviews with the research team captured their experiences of the intervention. The feasibility component of this trial examined recruitment via primary care and retention of participants, appropriateness of the intervention for older adults and the delivery of the intervention by a practice nurse. Discussion West End Walkers 65+ will determine the feasibility and pilot the efficacy of delivering a pedometer-based walking intervention through primary care to Scottish adults aged ≥65 years. The study will also examine the effect of the intervention on the well-being of participants and gain an insight into both participant and research team member experiences of the intervention. Trial registration number ISRCTN: ISRCTN70658148